Magnetic resonance imaging investigation of age‐related morphological changes in the pancreases of 226 Chinese. Issue 4 (11th December 2021) - Wang, Lu; Jia, Huihui; Lin, Guangwu; Zheng, Songbai
Abstract: Objective: To investigate the morphological changes with age in the pancreases of healthy individuals undergoing magnetic resonance imaging (MRI). Methods: The participants were selected from adults who were undergoing physical examinations from January 2017 to September 2020 at Huadong Hospital. They were divided according to age, as broken down by decades into seven groups ranging from 20 to 29 years to ≥80 years of age. There were 30 to 35 cases for each decade. They were then divided into a young and middle‐aged group (<60 years of age) and an elderly group (≥60 years of age). The morphological characteristics of the pancreases of each participant in the group were measured on magnetic resonance images. The characteristics included the pancreatic anteroposterior diameters and volumes. The relationships between the anteroposterior diameters of the pancreatic head, body, and tail and pancreatic volume and age were analyzed. Results: A total of 226 magnetic resonance images from 112 (49.56%) men and 114 (50.44%) women, aged 22–93 (54.68 ± 19.52) years. The age ranges of the seven groups consisted of the following: 20–29 years ( n = 33), 30–39 years ( n = 32), 40–49 years ( n = 32), 50–59 years ( n = 31), 60–69 years ( n = 35), 70–79 years ( n = 33) and ≥80 years ( n = 30). The age range and numbers of patients in the young and middle‐aged group was 22–59 (40.09 ± 10.88) years ( n = 128) and in the elderly group was 60–93 (73.74 ± 8.99) years ( n = 98). The MRI findings characteristic of aging included pancreatic atrophy (especially of the pancreatic tail), pancreatic lobulation, uneven signal intensity, fatty degeneration, and widening of the main pancreatic duct. The respective anteroposterior diameters of the pancreatic head, body, and tail and the pancreatic volumes peaked at 30 to 39 years as follows: 28.03 ± 4.45 mm, 24.10 ± 4.27 mm, 24.57 ± 4.94 mm, 98.54 ± 26.56 cm 3 ; and then gradually decreased to 19.05 ± 3.59 mm, 16.00 ± 3.81 mm, 13.83 ± 3.39 mm, 45.02 ± 9.15 cm 3 at ≥80 years, for respective decreases of 32.03%, 33.60%, 43.71%, and 54.31%. The respective anteroposterior diameters of the pancreatic head, body, tail, and pancreatic volume in the elderly patients were 21.45 ± 4.15 mm, 18.14 ± 4.09 mm, 16.81 ± 4.37 mm, and 59.02 ± 21.44 cm 3, which were significantly smaller than the respective corresponding measurements in the young and middle‐aged patients (26.09 ± 4.40 mm, 22.30 ± 4.42 mm, 22.08 ± 4.53 mm, and 88.32 ± 23.92 cm 3 ). The differences were statistically significant (t = 8.06, 7.24, 8.79, 9.54, respectively, p < 0.001). The anteroposterior diameters of the pancreatic head, body, tail, and pancreatic volume were negatively correlated with age ( r = −0.53, −0.47, −0.56, −0.57, respectively, p < 0.001). Conclusion: The anteroposterior diameters of the pancreatic head, body, tail, and the pancreatic volume all peaked at the age range of 30–39 years and then gradually decreased with increasing age. After the age of 60 years, pancreatic atrophy became increasingly obvious, with changes in shape and widening with age of the main pancreatic duct. Abstract : Research flow chart All subjects were 18 years, with normal BMI range, biochemical parameters and without acute and chronic pancreatitis, diabetes, pancreatic masses and other pancreatic diseases.